2018
DOI: 10.1111/iej.12985
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of various rotary and reciprocating systems with different surface treatments to remove gutta‐percha and an epoxy resin‐based sealer from straight root canals

Abstract: The Reciproc system was more effective than the Reciproc Blue and ProTaper Universal Retreatment systems during the removal of filling material from oval, straight canals, although none of the systems completely removed the filling material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
2
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 42 publications
4
33
2
6
Order By: Relevance
“…Novel endodontic instruments have been used in non-surgical endodontic retreatment, and ProTaper Gold endodontic rotary instruments and Reciproc Blue endodontic reciprocating instruments have demonstrated their effectiveness in root canal filling removal [22]; however, none has reported a complete root canal filling material removal from the root canal system. Bago et al reported a higher capability of the Reciproc endodontic reciprocating system to remove the root canal filling material from the root canal system than Reciproc Blue endodontic reciprocating system and ProTaper Retreatment endodontic rotary system [23]; however, none of these articles analyzed the efficacy of the endodontic rotary or reciprocating systems to remove a carrier-based root canal filling material. The GuttaCore carrier-based root canal filling material has demonstrated a high marginal sealing capability, especially in oval-shaped root canal systems; furthermore, it can penetrate to a depth of 96 µm and 48 µm into the dentinal tubules, located at 5 mm and 2 mm of the working length, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Novel endodontic instruments have been used in non-surgical endodontic retreatment, and ProTaper Gold endodontic rotary instruments and Reciproc Blue endodontic reciprocating instruments have demonstrated their effectiveness in root canal filling removal [22]; however, none has reported a complete root canal filling material removal from the root canal system. Bago et al reported a higher capability of the Reciproc endodontic reciprocating system to remove the root canal filling material from the root canal system than Reciproc Blue endodontic reciprocating system and ProTaper Retreatment endodontic rotary system [23]; however, none of these articles analyzed the efficacy of the endodontic rotary or reciprocating systems to remove a carrier-based root canal filling material. The GuttaCore carrier-based root canal filling material has demonstrated a high marginal sealing capability, especially in oval-shaped root canal systems; furthermore, it can penetrate to a depth of 96 µm and 48 µm into the dentinal tubules, located at 5 mm and 2 mm of the working length, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, reciprocating systems have been reported to be more effective than rotary systems for the removal of epoxy resin‐based sealers or calcium silicate‐based sealers (Monquilhott Crozeta et al 2016, Suk et al . 2017, Bago et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to several studies, approximately 10–49% of root canal walls remain uninstrumented as a result of rotary and reciprocating instrumentation (Gambill et al 1996, Siqueira et al 2013, Zhao et al 2014, Drukteinis et al 2019, De‐Deus et al 2019b). Additionally, the amount of remaining filling material after basic retreatment instrumentation ranges widely between 4% and 45% (Bernardes et al 2016, Crozeta et al 2016, Yilmaz et al 2018, Delai et al 2019, Kaloustian et al 2019) with the reduction rate ranging between 76% and 96% (Bago et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown a better performance with reciprocating instruments (18)(19), rotary (20)(21) and both presenting similar results (6,22). A possible explanation for the results found in the present study may be related to the design of the instruments.…”
Section: Discussionsupporting
confidence: 78%
“…Along with this, ProDesign Logic RT used 3x higher speed also contributed to this instrument penetrating more easily and achieving significantly faster working length. Studies in the literature comparing different kinematics uses rotational systems that present more than one instrument in the technique and are used at lower speeds while reciprocating systems are unique instruments (6,19,23). These variations may lead to results different from those found in the present study where the rotational system used had only a single instrument and at a speed of 900 RPM.…”
Section: Discussionmentioning
confidence: 56%